A project of an assembly table for an electric switchboards - Cieślak, Robert; Wysocki, Ireneusz; Piguła, Albert (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2017)
The paper presents a project of an assembly table designed for the ELEKTROBUDOWA S.A. company. The project constitutes one of the stages of implementing an assembly platform in this firm. The publication shows the ways of adjusting the platform to the final product, which is low, medium and high voltage switchboards produced in the ELEKTROBUDOWA S.A. The adjustment in turn is a vital point in the process of designing an assembly platform and approaching the pattern for a family of products. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)